The Ecophysiology of Guppy Fish (Poecilia reticulata) in the Pucung River, A Former Fossil Excavation Site: The ecophysiology of guppy fish in the Pucung river - Beanal, Yohanis; Nugroho, Rully Adi (Journal of Tropical Life Science, 2025)
Exposing land surfaces through fossil excavation activities can increase sediment loads and toxic chemicals that are discharged into water bodies. This can have negative effects on receiving environments and their habitats. The aim of this study was to evaluate the dry body weight and physiology (whole body lipid and protein contents) of guppy fish (Poecilia reticulata) in Pucung River, a former archaeological excavation site in Sangiran, Indonesia. Little is known about their physiology in this river. Guppy fish and water were sampled from eight sites along the Pucung River, two sites (Site 1 and Site 2) were situated upstream of the archeological excavation site, one site (Site 3) was at the archeological excavation site, and five sites (Site 4 - Site 8) were situated downstream of the archeological excavation site. The distance between the two sites was 500 m. The length and total weight of captured male fish were measured. Lipid and protein contents of male fish were determined gravimetrically, and the results were conveyed as Joules. A total of 240 male individuals were captured with a length between 1.24 and 3.95 cm. The weight of male guppies varied between 13.0 and 38.2 mg. Male guppies' average lipid and protein contents ranged from 0.0509 J to 0.2635 J and 0.0842 J to 0.1648 J, respectively. The smallest weights and lipid contents among individuals were found in the excavation site (Site 3) and a site downstream (Site 4). These individuals also had the smallest protein contents, along with those from Site 5 to Site 7. Fish dry weight and lipid content were positively correlated with water pH and dissolved oxygen, and negatively correlated with biological oxygen demand. These findings showed that guppy dry weight and lipid content may be utilized to assess the impact of human activities on river health.